2021
DOI: 10.1039/d1cc03767f
|View full text |Cite
|
Sign up to set email alerts
|

Helical mesoscopic crystals based on an achiral charge-transfer complex with controllable untwisting/breaking

Abstract: The development of synthetic helical structures from achiral molecules and stimuli-responsive shape transformations are vital for biomimetic understanding and mechanical actuators. The stimulus regarded as the force to induce the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In a recent paper, researchers described a twisted CTC crystal composed of pyrene and DTTCNQ (4,8-bis­(dicyanomethylene)-4,8-dihydrobenzo­[1,2-b:4,5-b′]-dithiophene) deposited from solution . Individual twisted helicoids were described, as in refs , .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, researchers described a twisted CTC crystal composed of pyrene and DTTCNQ (4,8-bis­(dicyanomethylene)-4,8-dihydrobenzo­[1,2-b:4,5-b′]-dithiophene) deposited from solution . Individual twisted helicoids were described, as in refs , .…”
Section: Discussionmentioning
confidence: 99%
“… 9 Recently, we prepared twisted achiral charge-transfer complex crystals of pyrene and 4,8-bis(dicyanomethylene)-4,8-dihydrobenzo[1,2- b :4,5- b ′]-dithiophene (DTTCNQ) via a self-assembly method in a polar solvent that functions due to the internal stress and solvent–solute interactions. 10 A phase transition from a dynamically stable phase to a thermodynamically stable phase induces the spontaneous stress relaxation of the untwisting. Later, Kahr et al reported a series of charge-transfer complexes with twisted morphologies synthesized from melts with a larger propensity to form twisted structures than the monocomponent systems, where the slightly rotated layers helped to increase the charge mobilities.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Crystals can undergo spontaneous twisting during their growth. [18][19][20][21][22] Extrinsic stimuli such as light, [23][24][25][26][27] heat, 28 and mechanical force 14,29,30 can also trigger the crystal twisting. However, there are currently no welldefined molecular design strategies for achieving twisted crystals and the intrinsic factors governing crystal twisting need to be investigated urgently.…”
Section: Introductionmentioning
confidence: 99%